Waste Management and Recycling Programs Empowering Environmental Sustainability: The Case of Gümüşhane - Külekçi, Gökhan; Güvendi, Aslıhan (Atlas Journal, 2023)
Gümüşhane, located in the northeastern part of Turkey, plays a significant role in pursuing environmental sustainability, especially concerning solid waste management and recycling practices. Solid waste management stands out as a crucial component in this process. The Municipality of Gümüşhane places great importance on recycling programs aimed at minimizing the environmental impacts of waste. This approach yields noteworthy results in terms of resource conservation. The separation and recycling of waste materials reduce the amount of raw materials required for the production of new goods, leading to energy and water savings while preserving natural resources. One prominent advantage of these programs is their ability to reduce the amount of waste stored in landfills, extending the operational lifespans of disposal sites and reducing the risk of harm to underground water sources. These initiatives generate employment within the community and contribute to the local economy, besides their ecological benefits. However, we face challenges such as budget constraints, deficiencies in waste collection, and a low level of awareness about zero waste practices. In conclusion, solid waste management and recycling programs in Gümüşhane make significant contributions to environmental sustainability, but closing the resource and public support gap is necessary to enhance their effectiveness.